2009
DOI: 10.1111/j.1524-4733.2008.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empiric Estimate of the Value of Life: Updating the Renal Dialysis Cost-Effectiveness Standard

Abstract: The value of a statistical year of life implied by dialysis practice currently averages $129,090 per QALY ($61,294 per year), but is distributed widely within the dialysis population. The spread suggests that coverage decisions using dialysis as the benchmark may need to incorporate percentile values (which are higher than the average) to be consistent with the Rawlsian principles of justice of preserving the rights and interests of society's most vulnerable patient groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
110
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(110 citation statements)
references
References 21 publications
(30 reference statements)
0
110
0
Order By: Relevance
“…However, investigators in a more recent analysis have estimated that the average ICER per QALY of dialysis in current practice compared with the next least costly alternative is $129,000, with a range of $65,496 to $488,360. 39 Furthermore, assessing the cost-effectiveness of a drug or intervention is just one part of a treatment plan that may include hospitalization costs, surgeries and procedures, radiotherapy, and indirect costs due to lost wages. It is, therefore, evident how difficult it is to establish a threshold ICER to help guide and formulate policy decisions.…”
Section: What Polices or Interventions Can Be Used To Lower The Cost mentioning
confidence: 99%
“…However, investigators in a more recent analysis have estimated that the average ICER per QALY of dialysis in current practice compared with the next least costly alternative is $129,000, with a range of $65,496 to $488,360. 39 Furthermore, assessing the cost-effectiveness of a drug or intervention is just one part of a treatment plan that may include hospitalization costs, surgeries and procedures, radiotherapy, and indirect costs due to lost wages. It is, therefore, evident how difficult it is to establish a threshold ICER to help guide and formulate policy decisions.…”
Section: What Polices or Interventions Can Be Used To Lower The Cost mentioning
confidence: 99%
“…A study by the same investigators of elderly nursing home patients starting dialysis revealed even worse results, with 87% of them dying or experiencing a functional decline in the first year after dialysis initiation (25). Not surprisingly, cost utility analyses reveal that elderly patients with ESRD have higher ICERs than younger patients (19,26).…”
Section: Restricting Access To Dialysismentioning
confidence: 99%
“…Traditionally, an intervention has been considered economically justified at #$50,000/QALY (18). Investigators recently estimated the ICER of dialysis compared with that of palliative care to be $110,814/QALY (19).…”
Section: How Will the Government Measure The Value Of Care?mentioning
confidence: 99%
“…The cancer risk in terms of DALY was obtained as 8.48×10 -7 per person per year (PPPY), which was lower than the USEPA guideline value of 1.0×10 -6 [27]. One DALY was associated with a loss of US$ 108,600 [28], which means one year of healthy human life costs US$ 108,600, indicating that the total financial burden for Saudi Arabia was US$ 2.72 million with the range of US$ 2.52 -2.91 million per year. …”
Section: Risks Of Thmsmentioning
confidence: 99%